Basics of Data Decision-making in Business - Pavić, Lazar (Interdisciplinary and Applied Konwledge for Green and Digital Logistics Processes, 2026)
In this chapter, the fundamental concepts necessary for successful business decision-making based on data are presented. The basic phases of research and fundamental concepts essential for effective decision-making are introduced: statistical population, units of analysis, representative sample, variables, measurement scales, and hypotheses. The importance of collecting primary and secondary data in business decision-making, along with proper tabular and graphical representation of data, is then emphasized. The chapter is concluded with guidance on selecting appropriate statistical analysis to confirm or reject properly formulated research hypotheses.